Forgiveness and life satisfaction at Umm Al-Qura University students in the Light of some variables - Al-Qathami, Saud Saad Mohammed; Al-Mafraji, Salem Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to know the forgiveness and the life satisfaction according to the two variables (academic achievement, income level) of Umm Al-Qura University students. The researcher used the descriptive relational approach to suitability for study purposes, where a random sample of 400 students from the College of Education was chosen. As for the research tools, the scale of forgiveness, prepared by Mullet (2007), translation and legalization of Al-Dossary (2012), and measure of satisfaction with life, prepared by El-Desouki (1999), legalization of El-Sherbiny (2009). The results indicated, First: The level of amnesty for Umm Al-Qura University students was high. Second: The level of satisfaction with life among Umm Al-Qura University students was high. Third: There is no statistically significant effect of the level of income on the dimensions of the pardon, and there is also no statistically significant effect of academic achievement on The dimensions of the pardon, and there is an interaction between the level of income and academic achievement on the second dimension, which is (sensitivity to circumstances), Fourth: The income level has a statistically significant effect on life satisfaction, as the differences are significant between low-income and high-income people in life-satisfaction in favor of high-income people, as well as there are differences between middle-income and low-income in life-satisfaction in favor of middle-income. Differences in life satisfaction between high and middle income. Also, the level of achievement has a statistically significant effect on life satisfaction between the level of achievement is acceptable and very good only, as well as the interaction between the level of income and the level of academic achievement in life satisfaction, Fifth: After the persistence of feelings of dissatisfaction with the amnesty scale is not statistically related to any dimension of satisfaction with life, while the second dimensions, “sensitivity to circumstances” and the third “desire to pardon, ” each of them is statistically significant with the dimensions of satisfaction with life and the overall degree of satisfaction with Life, except after the social assessment in the measure of life satisfaction, as it is not statistically related to them. The study recommends the need to take advantage of social media to develop the values ​​of satisfaction with life and forgiveness for students, And the necessity of designing counseling programs to develop the forgiveness for undergraduate students.